Evogliptin Suppresses Calcific Aortic Valve Disease by Attenuating Inflammation, Fibrosis, and Calcification - Bongkun Choi; Eun-Young Kim; Ji-Eun Kim; Soyoon Oh; Si-On Park; Sang-Min Kim; Hyuksu Choi; Jae-Kwan Song; Eun-Ju Chang (Cells, 2021)
Calcific aortic valve disease (CAVD) accompanies inflammatory cell infiltration, fibrosis, and ultimately calcification of the valve leaflets. We previously demonstrated that dipeptidyl peptidase-4 (DPP-4) is responsible for the progression of aortic valvular calcification in CAVD animal models. As evogliptin, one of the DPP-4 inhibitors displays high specific accumulation in cardiac tissue, we here evaluated its therapeutic potency for attenuating valvular calcification in CAVD animal models. Evogliptin administration markedly reduced calcific deposition accompanied by a reduction in proinflammatory cytokine expression in endothelial nitric oxide synthase-deficient mice in vivo, and significantly ameliorated the mineralization of the primary human valvular interstitial cells (VICs), with a reduction in the mRNA expression of bone-associated and fibrosis-related genes in vitro. In addition, evogliptin ameliorated the rate of change in the transaortic peak velocity and mean pressure gradients in our rabbit model as assessed by echocardiography. Importantly, evogliptin administration in a rabbit model was found to suppress the effects of a high-cholesterol diet and of vitamin D2-driven fibrosis in association with a reduction in macrophage infiltration and calcific deposition in aortic valves. These results have indicated that evogliptin prohibits inflammatory cytokine expression, fibrosis, and calcification in a CAVD animal model, suggesting its potential as a selective therapeutic agent for the inhibition of valvular calcification during CAVD progression.